Self-healing Characteristic of Concrete Containing Capillary Crystalline Waterproofing Material - Amran, Nur Aini; Kusbiantoro, Andri; Ismail, Nur Amalina Hanani (Progress in Engineering Application and Technology, 2025)
The self-healing properties of concrete are a key characteristic produced by capillary crystalline waterproofing material to mitigate microcracks. This study investigates the effects of varying (CCW) proportions (0, 0.5, 1.0 and 1.5 %) on M25 grade concrete, which was subjected to compressive strength tests to create controlled cracking. The concrete mix included coarse and fine aggregates, ordinary Portland cement, and capillary crystalline waterproofing material. The materials used included coarse and fine aggregates, ordinary Portland cement, and capillary crystalline waterproofing material. The experiment utilized 100mm x 100mm x 100mm cube moulds with curing periods of 28 and 56 days, and included 36 samples with varying percentages of capillary crystalline waterproofing material. In these studies, the analyse the crack-filling mechanism in concrete enhanced with capillary crystalline waterproofing material shows in mix proportion 1.0% CCW inclusion and makes that inclusion was the optimum number for self-healing. Furthermore, the study explored the self-healing capabilities of concrete with capillary crystalline waterproofing material and aiming to enhance the permeability within 56 days post-loading. The results emphasize the theoretical and practical benefits of capillary crystalline waterproofing material as an additive for producing durable and sustainable concrete structures.